Analisis Semiotika Komunikasi Visual Buku â€œMemahami Komikâ€ Scott McCloud - Patricia, Florens Debora (Jurnal Studi Komunikasi, 2018)
This research aims to finding ascpets of theory in Understanding Comics: The Invisible Art by Scott McCloud, using the analitical of semiotic research of Roland Barthes, by focusing on issues: 1) Visual narrative in Understanding Comics, 2) Visual language in Understanding Comics, and 3) Visual implications of theory in Understanding Comics for examples; comics book, comics research and journal of comics in 2010s above. The Narrative methodology is used for qualitative-interpretative, with sign analysis and text analysis as an object of research.